Cholesteric liquid crystal glass platinum acetylides. Issue 1698 (21st August 2014) - Cooper, Thomas M.; Burke, Aaron R.; Krein, Douglas M.; Ziolo, Ronald F.; Arias, Eduardo; Moggio, Ivana; Fratini, Albert; Garbovskiy, Yuriy; Glushchenko, Anatoliy V.
ABSTRACT: To prepare cholesteric liquid crystalline nonlinear optical materials with ability to be vitrified on cooling and form long time stability cholesteric glasses at room temperature, a series of platinum acetylide complexes modified with cholesterol has been synthesized. The materials synthesized have the formula trans -Pt(PR 3 )(cholesterol (3 or 4)-ethynyl benzoate)(1-ethynyl-4-X -benzene), whereR =Et, Bu orOct andX =H, F, OCH 3 andCN . A cholesteric liquid crystal phase was observed in the complexesR =Et, andX =F, OCH 3 andCN but not in any of the other complexes. WhenX =CN, a cholesteric glass was observed at room temperature which remained stable up to 130 °C, then converted to a mixed crystalline/cholesteric phase and completely melted to an isotropic phase at 230 °C. WhenX =F orOCH 3 the complexes were crystalline at room temperature with conversion to the cholesteric phase upon heating to 190 and 230 °C, respectively. In the seriesX =CN, OCH 3 andF, the cholesteric pitch was determined to be 1.7, 3.4 and 9.0 µ, respectively.